Pengaruh Kualitas Pelayanan, Store Atmosphere dan Penetapan Harga Terhadap Kepuasan Konsumen pada Senada Cafe Kota Garo, Kampar - Wilda Nirahma. S; Endang Sutrisna (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to determine the effect of service quality, store atmosphere, and pricing on customer satisfaction at Senada Cafe in Kota Garo, Kampar Regency. The method used in this research is quantitative method. The sample in this study amounted to 99 respondents who were consumers of Senada Cafe, who were taken with non-probability sampling techniques including incidental sampling. Data collection in this study was carried out through distributing questionnaires that had been tested for validity and reliability. Data analysis was carried out using simple linear regression and multiple regression through the SPSS version 29 program. Validity test, reliability test, multicollinearity test, heteroscedasticity test, simple linear regression test, t test, multiple linear regression test, F test and coefficient of determination (R2) test, coefficient of determination (R2). The results showed that the variables of service quality (X1), store atmosphere (X2), and pricing (X3) had a positive and significant effect on customer satisfaction (Y).